Associations Between the Modified Food Standard Agency Nutrient Profiling System Dietary Index and Cardiovascular Risk Factors in an Elderly Population - Khoury, Nadine; Gómez-Donoso, Clara; Martínez, María Ángeles; Martínez-González, Miguel Ángel; Corella, Dolores; Fitó, Montserrat; Martínez, J. Alfredo; Alonso-Gómez, Ángel M.; Wärnberg, Julia; Vioque, Jesús; Romaguera, Dora; León-Acuña, Ana; et al. (Frontiers in Nutrition, 2022)
Background: Helping consumers to improve the nutritional quality of their diet is a key public health action to prevent cardiovascular diseases (CVD). The modified version of the Food Standards Agency Nutrient Profiling System Dietary Index (FSAm-NPS DI) has been used in public health strategies to address the deleterious consequences of poor diets. This study aimed to assess the association between the FSAm-NPS DI score and CVD risk factors such as body mass index (BMI), waist circumference, plasma glucose levels, triglycerides levels, high-density lipoprotein (HDL) and low-density lipoprotein (LDL) cholesterol, and diastolic and systolic blood pressure. Methods: Dietary intake was assessed at baseline and after one-year of follow-up using a validated semi-quantitative food-frequency questionnaire. Dietary indices based on FSAm-NPS applied at an individual level were computed to characterize the diet quality of 5921 participants with overweight/obesity and metabolic syndrome from the PREDIMED-plus cohort. Associations between FSAm-NPS DI and CVD risk factors were assessed using linear regression models. Results: Compared to participants with a higher nutritional quality of diet (measured by a lower FSAm-NPS DI at baseline or a decrease in FSAm-NPS DI score after one-year), those participants with a lower nutritional quality of diet (higher FSAm-NPS DI or an increase in score) showed a significant increase in the levels of plasma glucose, triglycerides, diastolic blood pressure, BMI and waist circumference (β coefficient [95% confidence interval]; P for trend) (1.67 [0.43, 2.90]; <0.001; 6.27 [2.46, 10.09]; <0.001; 0.56 [0.08, 1.05]; 0.001; 0.51 [0.41, 0.60]; <0.001; 1.19 [0.89, 1.50]; <0.001, respectively). No significant associations in relation to changes in HDL and LDL-cholesterol nor with systolic blood pressure were shown. Conclusion: This prospective cohort study suggests that the consumption of food with higher FSAm-NPS DI score is associated with increased levels of several major risk factors for CVD. These findings support the use of FSAm-NPS as a nutrient profiling system in public health strategies such as front-of-pack labelling.